Demographic situation as a major factor to develop labour potential in rural areas - Roman Chornyi; Liubov Shevchuk (Cхід, 2013)
The article analyses the demographic situation in rural areas of Ukraine as a prerequisite of development of labour potential within their limits. It is shown that the demographic situation in rural areas of Ukraine is characterized, region by region, with the predominance of negative tendencies that are manifested in the decrease of rural population, general and natural. While the population in Ukraine has decreased in general from 46929525 to 45778534 over the period of 2006-2011 making a loss of 1150991 people, the rural population lost 714930 people (decreased from 15051815 to14336885 people), all regions being the losers. Special attention is paid to such regions as those of Chernihiv, Vynnitsia, Zhytomyr, Poltava where the natural basis for the reproduction of rural population had become narrower by 2011, and so has the labour resource. More peasants were born only in the Autonomous Republic of the Crimea and Thranscarpathian Region, and a rise in the natural growth of rural population had been observed the region of Rivne and Thranscarpathian one. The depopulation of rural areas is already limiting the possibilities of the physical base to increase a labour potential and it causes a real threat to the national security, to the genetic fund of the Ukrainian people and to the development of labour potential in general. The article stresses the necessity to work out and implement a reasonably weighed demographic policy in Ukraine as well as regional demographic policy so as to improve the demographic situation as a base to renew and develop the labour potential of rural areas